DIETS CONTAINING SELENIZED YEAST, SELENATE, CARNOSIC ACID AND FISH OIL CHANGE THE CONTENT OF FATTY ACIDS, TOCOPHEROLS AND CHOLESTEROL IN THE SUBCUTANEOUS FAT OF LAMBS - K. A. Krajewska-Bienias; M. Czauderna; M. Marounek; A. J. Rozbicka-Wieczorek (Journal of Animal and Plant Sciences, 2017)
Male lambs were divided into 5 groups of 6 animals. For 35 days each group was fed one of the following diets: control diet containing 3% rapeseed oil (RO); ROFO diet containing 2% RO and 1% fish oil (FO); CA diet with the addition of 2% RO, 1% FO and 0.1% carnosic acid (CA); CASeY diet with the addition of 0.35 ppm selenium (Se)in the form of selenized-yeast (SeY) to the CA diet; CASeVI diet with the addition of 0.35 ppm Se in the form of selenate (SeVI) to the CA diet. Subcutaneous adipose tissue (SAT) samples were collected from lambs. The experimental diets decreased the C15:0 and C18:0 contents and the sum of conjugated linoleic acid isomers in the SAT when compared to the control diet. The content of long-chain polyunsaturated fatty acids (LPUFA), including n-3LPUFA in the SAT, were most effectively increased by the ROFO diet. The CASeVI diet most effectively increased the content of cholesterol in the SAT. The CASeY and CASeVI diets most effectively increased the content of all tocopherols in the SAT. Oxidative stress in the SAT was most effectively reduced by the CA diet. The ROFO diet increased oxidative stress in the SAT relative to the control diet.
Keywords: fatty acid; fish oil; carnosic acid; selenium; tocopherols; subcutaneous adipose tissue; lambs